The Role of Colonialism in the Transformation of the Indigenous Naming System of the Amuthambi of Tharaka Nithi County, Kenya, 1920-1963 - Njagi, Serah Njoki; Muraya, Martha W.; Ireri, Humphery K. (International Journal of Culture and History, 2023)
Naming is a universal phenomenon and as old as human history. In traditional Africa, naming was complex and authentic. The cultural values, traditions, beliefs and norms were highly linked with the African naming. However, colonial policies, practices and activities such as taxation, cash crop farming, wage labour, modern health care, Christianity and Western education impacted heavily the traditional naming system of the Amuthambi. The current research focused on establishing the role of colonialism in the transformation of the indigenous naming system of the Amuthambi from 1920 to 1963. The research was conducted among the Amuthambi of Mitheru and Muthambi wards in Tharaka Nithi County, Kenya. The study employed the structural functionalism theory and the acculturation theory. A descriptive research design based on a qualitative approach was used to describe the phenomena. A purposive sampling procedure and snowballing technique were employed to identify the respondents. The concept of data saturation was applied and the information was mainly gathered using primary sources including; oral sources and archival. Secondary sources including books, journals, dissertations, articles, thesis and electronics were also used to corroborate the primary data. An interview guide was used to aid in collecting the oral data. Data was analyzed thematically and later presented in narrative form. The findings of the study established that the introduction of taxation, forced labour, cash crop farming, wage economy, western education, modern healthcare and Christianity weakened the traditional naming principles, patterns and procedures and a new naming system emerged. At the end of the colonial period the society became more individualistic, and matters about the birth and naming of the child became more of a private affair contrary to the traditional setup. Consequently, a new version of the naming system that characterizes the hybridity of both traditional and modern naming systems became evident among the Amuthambi. The study documents the historical influence of colonialism on African cultural practices by investigating the influence of colonialism on the transformation of the indigenous naming system of the Amuthambi.